Evidence of blood stage efficacy with a virosomal malaria vaccine in a phase IIa clinical trial. - Fiona M Thompson; David W Porter; Shinji L Okitsu; Nicole Westerfeld; Denise Vogel; Stephen Todryk; Ian Poulton; Simon Correa; Claire Hutchings; Tamara Berthoud; Susanna Dunachie; Laura Andrews; et al. (PLoS ONE, 2008)
BACKGROUND:Previous research indicates that a combination vaccine targeting different stages of the malaria life cycle is likely to provide the most effective malaria vaccine. This trial was the first to combine two existing vaccination strategies to produce a vaccine that induces immune responses to both the pre-erythrocytic and blood stages of the P. falciparum life cycle. METHODS:This was a Phase I/IIa study of a new combination malaria vaccine FFM ME-TRAP+PEV3A. PEV3A includes peptides from both the pre-erythrocytic circumsporozoite protein and the blood-stage antigen AMA-1. This study was conducted at the Centre for Clinical Vaccinology and Tropical Medicine, University of Oxford, Oxford, UK. The participants were healthy, malaria naïve volunteers, from Oxford. The interventions were vaccination with PEV3A alone, or PEV3A+FFM ME-TRAP. The main outcome measure was protection from malaria in a sporozoite challenge model. Other outcomes included measures of parasite specific immune responses induced by either vaccine; and safety, assessed by collection of adverse event data. RESULTS:We observed evidence of blood stage immunity in PEV3A vaccinated volunteers, but no volunteers were completely protected from malaria. PEV3A induced high antibody titres, and antibodies bound parasites in immunofluorescence assays. Moreover, we observed boosting of the vaccine-induced immune response by sporozoite challenge. Immune responses induced by FFM ME-TRAP were unexpectedly low. The vaccines were safe, with comparable side effect profiles to previous trials. Although there was no sterile protection two major observations support an effect of the vaccine-induced response on blood stage parasites: (i) Lower rates of parasite growth were observed in volunteers vaccinated with PEV3A compared to unvaccinated controls (p = 0.012), and this was reflected in the PCR results from PEV3A vaccinated volunteers. These showed early control of parasitaemia by some volunteers in this group. One volunteer, who received PEV3A alone, was diagnosed very late, on day 20 compared to an average of 11.8 days in unvaccinated controls. (ii). Morphologically abnormal parasites were present in the blood of all (n = 24) PEV3A vaccinated volunteers, and in only 2/6 controls (p = 0.001). We describe evidence of vaccine-induced blood stage efficacy for the first time in a sporozoite challenge study.